The Histone-Fold Protein CHRAC14 Influences Chromatin Composition in Response to DNA Damage. - Mathew, V.; Pauleau, A.L.; Steffen, N.; Bergner, A.; Becker, P.B.; Erhardt, S. (Cell reports, 2014)
Chromatin reorganization and the incorporation of specific histone modifications during DNA damage response are essential steps for the successful repair of any DNA lesion. Here, we show that the histone-fold protein CHRAC14 plays an essential role in response to DNA damage in Drosophila. Chrac14 mutants are hypersensitive to genotoxic stress and do not activate the G2/M cell-cycle checkpoint after damage induction. Even though the DNA damage repair process is activated in the absence of CHRAC14, lesions are not repaired efficiently. In the absence of CHRAC14, the centromere-specific histone H3 variant CENP-A localizes to sites of DNA damage, causing ectopic kinetochore formation and genome instability. CENP-A and CHRAC14 are able to interact upon damage. Our data suggest that CHRAC14 modulates chromatin composition in response to DNA damage, which is required for efficient DNA damage repair in Drosophila.